Komunikasi Terapeutik Untuk Meningkatkan Kemampuan Berbicara Anak Gangguan Autis Spektrum Disorder (ASD) Di UPTD Pusat Layanan Disabilitas dan Pendidikan Inklusif Surakarta - Febriyaningrum, Brigitha Kartika; Wangi, Maya Sekar; Widiyowati, Estu (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Humans are social creatures in the sense that they cannot live alone and continuously with other humans. Humans need to interact, live in groups or need help from others. Of course, with children with special needs such as children with Autism Spectrum Disorder (ASD) who have limitations in interacting and communicating due to constraints from themselves. With the limitations they have, as parents of ASD children, they should be able to provide all forms of special education or therapy so that the child can improve their speaking and interacting abilities. Therapeutic actions with competent handling will improve ASD children. UPTD Center for Disability Services and Inclusive Education Surakarta is a place where children with special needs can get free therapy education. UPTD PLDPI Surakarta provides therapy in the form of speech therapy, behavioral therapy, occupational therapy and food therapy for children with Autism Spectrum Disorder (ASD). Speech therapy by therapists is a therapeutic action carried out at UPTD PLDPI Surakarta to improve the speaking and interacting abilities of ASD children. Using therapeutic communication in the form of therapeutic communication by therapists can help ASD children feel comfortable and feel confident if they can carry out therapeutic actions with a sense of security. So that ASD children who are guided by therapists when carrying out speech therapy properly will make ASD children more able to improve their speaking skills. Keywords: Therapeutic Communication, Children with Autism Spectrum Disorder (ASD), Speech Therapy, UPTD Center for Disability Services and Inclusive Education Surakarta.